Построение оценок решений в модели противоопухолевого иммунитета с импульсными возмущениями - Марценюк, В.П.; Багрий-Заяц, О.А. (Проблемы управления и информатики, 2013)
Запропоновано модель протипухлинного імунітету з імпульсними збуреннями щодо популяції проліферуючих клітин. Отримано асимптотичні оцінки розв’язків рівнянь. Оцінки будуються на основі імпульсних диференціальних нерівностей для функцій типу Ляпунова. A model of antitumor immunity with impulsive perturbations with respect to the population of proliferating cells is proposed. The asymptotic estimates for solutions of the equations are obtained. The estimates are based on impulsive differential inequalities for Lyapunov-type functions.